DEPLETION AND CONTAMINATION OF DRINKING WATER AQUIFERS UNDER INTENSIVE EXPLOITATION ON THE TERRITORY OF KYIV - Koshliakov, O.; Dyniak, O.; Koshliakova, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Consider the question of change of hydrodynamic condition of aquifers and complexes resulting from violations of the exploitation and protection of groundwater in Kyiv. The change of state drinking water aquifer under intensive use. The basic patterns of depletion and contamination of potable drinking ground water associated with man-made stress on the aquifers.